Prompt to Podcast: Reimagining Assessment with Generative AI - Patrick Buckland; Rebecca Purcell (Irish Journal of Technology Enhanced Learning)
In this case study, we outline a creative approach to integrating generative artificial intelligence (GenAI) into two assessments within an undergraduate organisational behaviour module. This approach promotes higher-order cognitive skills while upholding academic rigour and remaining true to assessing the module’s learning outcomes. In our first assessment, students were required to use GenAI to draft a structured review of an academic article on workplace diversity. A central characteristic was the iterative process of developing and refining prompts required to guide the GenAI towards the desired output, promoting the development of prompt engineering skills. In the second assessment, we outline how groups of students created an audio podcast based on a classical organisational experiment using GenAI to simulate an interview with the experiment’s original researcher, achieved through AI-driven role-play. These examples demonstrate how AI can be positioned not only as a tool but as a collaborative partner in encouraging critical thinking, creative exploration, and digital literacy.